Learning Management System Training at Postgraduate School Ibn Khaldun University Bogor - Rudi Hartono; Qurroh Ayuniah; Jaih Mubarak (Asosiasi Profesi Multimedia Indonesia, 2024)
Learning Management System (LMS) training aims to introduce and improve mastery of the Learning Management System for lecturers and students. Training was carried out at the Postgraduate School of Ibn Khaldun University, Bogor. This training is part of community service activities which is a concrete manifestation of academics' contribution to improving the quality of education in Indonesia. The training was held on June 15 2024 with the number of participants involved being 25 people who were students and lecturers at the Postgraduate School of Ibn Khaldun University, Bogor. The training results showed a 90% increase in participants' understanding and ability to use the Learning Management System. It can be concluded that the Learning Management System training at the Graduate School of Ibn Khaldun University Bogor succeeded in increasing the understanding and ability of lecturers and students to use the Learning Management System. This training proves that with the right guidance, the use of technology in education can be optimized. In the future, it is hoped that similar training can be held regularly to ensure that the entire academic community can make maximum use of the LMS in the learning process.